2013
DOI: 10.1177/0361684312470436
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Sexist Events and Psychological Distress of Sexual Minority Women of Color

Abstract: Scholars have argued that much of the sexism literature has not acknowledged diversity among women, and they have called for more attention to the intersectionality of the multiple marginalized identities of sexual minority women of color (WOC) in particular. With a sample of 182 sexual minority WOC, we examined (a) the links between perceived lifetime and recent sexist events and psychological distress and (b) the potential moderating role in these relations of womanism (a perspective of feminism that recogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 53 publications
(72 reference statements)
2
49
0
1
Order By: Relevance
“…In the context of mental health services, cultivating providers’ awareness and clinical skills around intersecting marginalized social statuses and encouraging inquiry about clients’ experiences of discrimination will aid in the accuracy of case formulations and provision of more appropriately nuanced care (Carr et al, 2014; DeBlaere & Bertsch, 2013; Szymanski, 2005). Providers ought to contextualize a client's presenting problems within broader sociohistorical injustices and can draw on feminist and womanist perspectives in approaching therapy (Carr et al, 2014; DeBlaere & Bertsch, 2013). Supporting a client's identification and deconstruction of stigmatizing cultural messages around race, gender, and/or sexual orientation may help to interrupt or counteract the internalization of such stigma.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the context of mental health services, cultivating providers’ awareness and clinical skills around intersecting marginalized social statuses and encouraging inquiry about clients’ experiences of discrimination will aid in the accuracy of case formulations and provision of more appropriately nuanced care (Carr et al, 2014; DeBlaere & Bertsch, 2013; Szymanski, 2005). Providers ought to contextualize a client's presenting problems within broader sociohistorical injustices and can draw on feminist and womanist perspectives in approaching therapy (Carr et al, 2014; DeBlaere & Bertsch, 2013). Supporting a client's identification and deconstruction of stigmatizing cultural messages around race, gender, and/or sexual orientation may help to interrupt or counteract the internalization of such stigma.…”
Section: Discussionmentioning
confidence: 99%
“…A limited number of quantitative studies have examined the link between self-reported experiences of discrimination and mental health among sexual minority women of color (DeBlaere & Bertsch, 2013; DeBlaere et al, 2014; Selvidge, Matthews, & Bridges, 2008; Szymanski & Meyer, 2008; Wilson et al, 2011), even fewer of which have focused on Black sexual minority women in particular (Szymanski & Meyer, 2008; Wilson et al, 2011). Generally, discrimination has been measured separately by race, gender, and/or sexual orientation, and often these different forms of discrimination have been examined simultaneously in an additive model.…”
Section: Discrimination and Mental Healthmentioning
confidence: 99%
See 2 more Smart Citations
“…Feminist identification also has been shown to protect women against negative effects of sexism on various mental health outcomes, including psychological distress and disordered eating (for a review, see Szymanski & Moffitt, 2012). Finally, DeBlaere and Bertsch (2013) found that womanist identification, which is inclusive of racial/ethnic, gender, and sexual orientation identities, played a buffering role in the link between sexism and psychological distress among African American sexual minority women.…”
Section: Identity Centrality As a Moderator In Predicting Psychological Distressmentioning
confidence: 99%